1955
DOI: 10.1113/jphysiol.1955.sp005274
|View full text |Cite
|
Sign up to set email alerts
|

Inulin space and fibre size of stimulated rat muscle

Abstract: If a limb of an anaesthetized animal is intermittently tetanized for a few minutes, the muscles soon become swollen, turgid and pink, and the water content increases considerably. Such effects might be produced by swelling of the fibres or by extracellular and circulatory changes. In this study it is shown that the increased inulin space partly accounts for the rise in water content on stimulation. In addition, measurement of fibre diameter showed no significant increase after tetanization. These results have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

1964
1964
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…The extracellular space in the rat diaphragm tends to increase with time, even in thin diaphragms maintained in vitro under favourable conditions (Creese & Northover, 1961). The muscle fibres themselves do not seem to undergo a detectable change in volume (Creese, 1954;Creese, D'Silva & Hashish, 1955). In this context the present findings, that the thickness of the diaphragms increases with time and that the tortuosity of the diffusion channels through the extracellular compartment decreases greatly, are explicable at least on a qualitative basis.…”
Section: Discussionmentioning
confidence: 57%
“…The extracellular space in the rat diaphragm tends to increase with time, even in thin diaphragms maintained in vitro under favourable conditions (Creese & Northover, 1961). The muscle fibres themselves do not seem to undergo a detectable change in volume (Creese, 1954;Creese, D'Silva & Hashish, 1955). In this context the present findings, that the thickness of the diaphragms increases with time and that the tortuosity of the diffusion channels through the extracellular compartment decreases greatly, are explicable at least on a qualitative basis.…”
Section: Discussionmentioning
confidence: 57%
“…To date much work on intramuscular transport has focused on measuring volumetric changes in interstitial space or total tissue volume induced by strain or contraction using tritiated water (Cappelli et al, 1981); molecular markers like inulin (Cappelli et al, 1981, Creese et al, 1955); albumin (Baker and Davis, 1974, Ward et al, 1996); or solutes like EDTA (Ward et al, 1996), sodium, and potassium (Sreter, 1963a, 1963b). Studies have measured contraction-induced diffusion of water (Trombitas et al, 1993) or myoglobin (Papadopoulos et al, 2000), but only intracellularly in single myofibers.…”
Section: Discussionmentioning
confidence: 99%
“…O'Keefe et al (36) have attempted to use histological point-counting methods to this end, estimating that the capillary-to-large-vessel volume ratios were ~27.2:4.9 or over 5-fold in normal dogs and 26.8:5.8 or ~4.5-fold in hypertrophied hearts. It would be useful to know the constancy of V ISF /V P , especially for organs with highly variable flow; for example, Creese et al (15) observed large changes in both inulin space (V ECF and blood space in stimulated skeletal muscle. Another source of variation is the form and stage of development of the organ; e.g., Burr and McLennan (14) observed that the interstitial space is much larger in small skeletal muscles than in large ones.…”
Section: Discussionmentioning
confidence: 99%
“…It is close to the value of 0.956 obtained by Effros and Chinard (16) for dog plasma. Therefore the interstitial water content (V ISF W ) would be 0.95 V ISF and cellular water (V CW ) would be (15) where 0.73 is the water content of erythrocytes in the dog (16).…”
Section: Calculationsmentioning
confidence: 99%